Two highly stable inorganic–organic hybrid 3D frameworks based on Cu–Ln incorporated polyoxometalates for selective dye removal and proton conduction. Issue 16 (7th April 2021) - Zhang, Rong-Tao; Xiao, Hui-Ping; Li, Zhong; Wang, Min; Xie, Yu-Feng; Ye, Yi-Da; Li, Xin-Xiong; Zheng, Shou-Tian
Abstract : Two highly stable inorganic–organic hybrid 3D TM–Ln incorporated POM-based framework materials have been successfully synthesized. The compounds can not only exhibit moderate proton conductivity but also selectively adsorb cationic dyes. Abstract : Two novel inorganic–organic hybrid 3D TM–Ln incorporated POM-based frameworks, H2 [Cu2 OL3 (H2 O)2 ][Ce(L)(H2 O)3 (PW11 O39 )]·17H2 O (1 ) and H4 [CuL3 ]2 [Ln(H2 O)3 (PW11 O39 )]2 ·28H2 O (2 ) (L = 4, 4′-bipyridine), were hydrothermally synthesized at different temperatures. Structural analysis reveals that both compounds are constructed from [Ln(PW11 O39 )] 4− polyoxoanions and different copper complexes. Interestingly, in compound 1, 2D copper complex layers and 1D chain [Ln(PW11 O39 )] 4− polyoxoanions interconnect to form a 3D framework. In contrast, in compound 2, 1D copper complex chains join the 2D [Ln(PW11 O39 )] 4− layers to give rise to a 3D framework. Both compounds exhibit excellent chemical stability. Furthermore, the dye adsorption and proton conduction properties of both compounds were also investigated. The conductivities of 1 and 2 are 3.175 × 10 −4 S cm −1 and 1.750 × 10 −4 S cm −1 at 85 °C and 98% RH, respectively. Dye adsorption studies indicate that they can selectively adsorb cationic dyes MB, CV and BR over anionic dyes MO, AO and large cationic RhB.